Need for Revamping Information Technology Laws in India - Walia, Ivneet Kaur; Kumar, Dinesh (Brawijaya Law Journal : Journal of Legal Studies, 2021)
Homo Sapiens have a distinct characteristic of being superior to other creatures. They owe this superiority not only because they have the power to reason and rationalize but also because they have a tendency to organize themselves as a congregation, which can work in a group at a large scale. The human instinct to improvise on its own inventions, have today resulted in mutation of a world from the stage of abacus to the era of Robotics. For the sake of avoiding chaos and maintaining the sovereignty, every nation strives to eradicate the fear of dominance by the selected elite and hence the need of regulations and the law. The aim of the paper is to highlight the grey areas and limitations existent in Information Technology Laws and focusing on the emerging domains of cyberspace. Its also aims to draw the attention by the policymakers and the legislators to understand the need for amending the Information Technology Act, 2000 for including legal provisions related to emerging issues in cyber space. The analytical research method is used to collect the data based on a systematic review of the existing sources of information and involved qualitative research to analyze the information. The conclusion and suggestions of this paper will definitely be helpful in either drafting or amending a comprehensive law relating to IT keeping in view the evolving technologies and their applications.